PROFITABILITY ANALYSIS OF SMALL-SCALE CATTLE FATTENING IN MAIDUGURI METROPOLIS, BORNO STATE, NIGERIA - Ameh, B. O.; Effiong, M. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analysed the profitability and efficiency of small-scale cattle fattening enterprises in Maiduguri Metropolis, Borno State, Nigeria. Primary data were collected from 108 cattle fatteners using a structured questionnaire through a multistage sampling technique. Data were analysed using descriptive statistics, gross margin analysis, and the stochastic profit frontier (SPF) model. Results from the profitability analysis, computed on a per-cattle basis, revealed a mean total variable cost of ₦346,293 and total revenue of ₦446,460, resulting in a gross margin of ₦100,167 and a net profit of ₦95,807 per cattle. The benefit–cost ratio of 1.27 and return on investment of 27.32% indicate that cattle fattening is economically viable in the study area. The SPF results showed that feeder cattle purchase price and feed cost significantly reduced profit, while education, experience, access to credit, and herd size positively influenced profitability. The estimated gamma value (0.72) indicated that 72% of the variation in gross margin was due to profit inefficiency. The mean profit efficiency score of 0.74 suggests that fatteners could increase profits by about 26% if operating at full efficiency with existing technology. The findings revealed that the major challenges confronting small-scale cattle fatteners were predominantly cost-related. High feed costs constituted the most critical constraint (20.6%), closely followed by the high cost of feeder cattle (19.0%), together accounting for nearly 40% of total responses and highlighting the capital-intensive nature of the enterprise. Limited access to credit ranked third (15.2%), reflecting persistent financial barriers that hinder enterprise expansion and the adoption of improved production practices. The study concludes that small-scale cattle fattening in Maiduguri Metropolis is profitable but constrained by high input costs and institutional limitations. Policy measures aimed at reducing feed costs, improving access to credit, and strengthening extension and veterinary services are essential to enhance profitability and sustainability.